Anthropology and health - National Seminar on 'Anthropology; Unveiling the Mystique' (2015 : New Delhi, India); Sinha, Rashmi; Indira Gandhi National Open University (Jaipur : Rawat Publications, 2019)
Contributed papers from National Seminar on 'Anthropology; Unveiling the Mystique' organized under the aegis of Indira Gandhi National Open University from 28-29 October 2015 at New Delhi.
Keywords: Medical anthropology -- India -- Congresses; Anthropology -- Health aspects -- India -- Congresses